2007
DOI: 10.1016/j.molstruc.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-polarization dynamics in polycrystalline samples

Abstract: We observe non-monotonic development of the 13 C magnetization in polycrystalline samples of glycine, sucrose, and adamantine during cross-polarization. We demonstrate, by fitting the time dependence, that the development quantitatively results from dipolar oscillations. To fit the data quantitatively requires one to assume two types of spindiffusion behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 41 publications
(63 reference statements)
2
22
0
Order By: Relevance
“…For a better data fitting, the authors modified the original CP model from Müller et al 20 in order to account for the proton spin lattice relaxation time and for all the possible crystallite orientations relative to the applied magnetic field. With this new approach, Taylor et al 17 showed that a nonmonotonic cross polarization can explain better the CP dynamics in polycrystalline molecules.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a better data fitting, the authors modified the original CP model from Müller et al 20 in order to account for the proton spin lattice relaxation time and for all the possible crystallite orientations relative to the applied magnetic field. With this new approach, Taylor et al 17 showed that a nonmonotonic cross polarization can explain better the CP dynamics in polycrystalline molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The aims of the present paper are: 1) to study the CP dynamics of two humic substances (from a soil sample and a coal sample) by applying the model proposed by Taylor et al 17 modified in order to account for the natural heterogeneity and amorphism of NOM; 2) to suggest a possible conformation in the solid state of the two humic substances.…”
Section: Dynamics Of Cross Polarization Inmentioning
confidence: 99%
See 3 more Smart Citations